Target-balances: The Greek examples - Malte Krueger (Research On Money in the Economy (ROME), 2013)
This article looks at the evolution of the Target balance of the Greek central bank. It is shown that in the first 18 months 'after Lehman', lending policy has been relatively lax, contributing to the increase of Target deficits. However, from spring 2010 onwards, there has been a slowburning bank run. Greek depositors converted their deposits into cash or transferred them to core countries such as Germany. Without the help of the Eurosystem, such a massive withdrawal would have led to the immediate failure of Greek banks and economic standstill in Greece. In this situation, the Eurosystem has performed its role as lender of last resort, as it should.
Keywords: E50; E58; E63; F32; F34; 330; Currency union; Balance of payments; Bailout; Eurosystem; Target